Voices revealed: A case for oral history in adult education research - Kimberly A. Townsend (Adult Education Research Conference, 1993)
This paper presents an argument for the use of oral history in adult education research. It discusses the concepts of "voice"; the techniques of oral history; and provides examples of oral history sources